Association between coping strategies and professional quality of life in nurses and physicians during COVID‐19: A cross‐sectional study. (26th October 2022) - Calegari, Jessica Graziella; Russo, Selena; Luciani, Michela; Strepparava, Maria Grazia; Di Mauro, Stefania; Ausili, Davide
Abstract: Aim: To explore the associations between coping strategies (social support, avoidance strategies, positive attitude, problem orientation, and transcendent orientation) and professional quality of life (compassion satisfaction, burnout, and secondary traumatic stress) of nurses and physicians during COVID‐19. Background: Little is known about the association between the way health care workers cope with stress and their professional quality of life during the unusual circumstances that the COVID‐19 pandemic imposed. Methods: A single‐centre cross‐sectional observational study was conducted with health care professionals ( n = 143). The Professional Quality of Life scale Version 5 and the Italian Version of the Coping Orientations to the Problems Experienced measured the professional quality of life and coping strategies, respectively. Results: Avoidance, problem orientation and social support coping worsened professional quality of life, whereas a positive attitude improved it. Conclusions: This study on the relationship between coping strategies and the professional quality of life during health emergencies like the COVID‐19 pandemic can inform interventions aiming to foster functional coping strategies in health care personnel to sustain their professional quality of life. Implications for Nursing Management: Identifying people at greater risk of burnout and secondary traumatic stress can guide tailored interventions to improve health care workers' wellbeing. Increased professional quality of life might turn in improved quality of care and reduced absenteeism and intention to leave.